Soil Fertility Changes With Climate and Island Age in Galápagos: New Baseline Data for Sustainable Agricultural Management - Strahlhofer, Matthias; Gerzabek, Martin H.; Rampazzo, Nicola; Couenberg, Paulina M.; Vera, Evelyn; Salazar Valenzuela, Xavier; Zehetner, Franz (Frontiers in Environmental Science, 2021)
While the extended absence of human influence has led to matchless natural conditions on the Galápagos archipelago, agricultural activities on the inhabited islands are increasingly affecting soil health and functioning. However, a systematic assessment of the agricultural soils on the Galápagos Islands is still absent. Plate tectonics and hotspot volcanism cause an eastward drift of the archipelago and result in a west-to-east soil age gradient from approx. 1 to 1,000 ka. In addition, precipitation regimes change from arid to humid with elevation on the higher-standing islands. The objective of this study was to investigate differences in soil fertility parameters and Mehlich (III)-extractable nutrient levels along these gradients in order to provide baseline information for sustainable agricultural management. Topsoil samples (0–20 cm) from 125 farms of the islands Isabela, Santa Cruz and San Cristóbal were analyzed. Gravel and sand content, pH, electrical conductivity, cation exchange capacity, base saturation, soil organic C and total N content tended to decrease with increasing island age, while clay content, soil macroaggregate stability, plant-available water and bulk density increased. Mehlich (III)-extractable base cations Ca, K, Mg and Na as well as P, Fe and Zn showed a decreasing tendency from the youngest to the oldest island, while Mn increased with island age. Mehlich (III)-extractable Cu and Na reached their highest levels on the most intensively farmed, intermediate-aged island Santa Cruz, likely related to anthropogenic inputs and irrigation with brackish water, respectively. Changes along the altitudinal climate gradient within the studied islands were most significant for soil pH, base saturation, and Mehlich (III)-extractable Ca and Mn. Our results highlight the importance of site-specific agricultural management to account for the strong heterogeneity in soil parameters among and within the Galápagos archipelago. The data provided herein shall serve as a baseline for targeted future management strategies to avoid soil degradation, restore and maintain soil functioning and, hence, sustain the soils’ provision of ecosystem services in this unique archipelago.